A week-48 randomized phase-3 trial of darunavir/cobicistat/emtricitabine/tenofovir alafenamide in treatment-naive HIV-1 patients. (17th July 2018) - Eron, Joseph J.; Orkin, Chloe; Gallant, Joel; Molina, Jean-Michel; Negredo, Eugenia; Antinori, Andrea; Mills, Anthony; Reynes, Jacques; Van Landuyt, Erika; Lathouwers, Erkki; Hufkens, Veerle; Jezorwski, John; et al.
Abstract : Objectives: To investigate efficacy and safety of a single-tablet regimen of darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg vs. darunavir/cobicistat plus emtricitabine/tenofovir disoproxyl fumarate (TDF) (control) in antiretroviral-treatment-naive, HIV-1-infected adults. Design: Phase-3, randomized, active-controlled, double-blind, international, multicenter, noninferiority study (NCT02431247). Methods: Seven hundred and twenty-five participants were randomized (1 : 1) to D/C/F/TAF (362) or control (363). The primary objective was to demonstrate noninferiority of D/C/F/TAF vs. control for percentage viral load less than 50 copies/ml (FDA-snapshot analysis) at 48 weeks (10% margin). Results: At week 48, D/C/F/TAF was noninferior to control (91.4 vs. 88.4% achieved viral load <50 copies/ml, respectively; difference 2.7%; 95% CI −1.6 to 7.1; P  < 0.0001), with 4.4 vs. 3.3% of patients, respectively, having viral load greater or equal to 50 copies/ml. No treatment-emergent mutations associated with darunavir or TAF/TDF resistance were observed in either group. One patient (D/C/F/TAF) was identified with M184I/V conferring resistance to emtricitabine. Incidences of grades 3 and 4 adverse events (5 vs. 6%), serious adverse events (5 vs. 6%) and adverse event-related discontinuations (2 vs. 4%) were low and similar between groups. Mean decrease in urine protein/creatinine ratio was greater with D/C/F/TAF than control (−22.42 vs. −10.34 mg/g, P  = 0.033). Mean percentage change in bone mineral density with D/C/F/TAF vs. control was 0.21 vs. −2.73%, P  < 0.0001 (hip), −0.68 vs. −2.38%, P  = 0.004 (lumbar spine), and −0.26 vs. −2.97%, P  < 0.0001 (femoral neck). Median change from baseline in total cholesterol/HDL-cholesterol ratio was 0.20 vs. 0.08, P  = 0.036. Conclusion: D/C/F/TAF achieved a high virologic suppression rate (91.4%) and was noninferior to darunavir/cobicistat with F/TDF. D/C/F/TAF also demonstrated the bone and renal safety advantages of TAF in combination with darunavir/cobicistat. Abstract : Supplemental Digital Content is available in the text